The Influence of Excellent Service on User Satisfaction in the Technical Implementation Unit of the Universitas Negeri Makassar Library - Selmiani Selmiani; Risma Niswaty; Muh. Nasrullah (Asha Publishing, 2024)
The quality of library services refers to the needs of users. Therefore, good service is a service that can meet the needs and desires of its users. So a good library is a library that is able to provide services to every user quickly, accurately and satisfactorily. The success of a library can be measured using the frequency of borrowing library materials and the level of user satisfaction, therefore the needs and requests of users need to be considered by the library. This research uses quantitative research with a population of 220 users, with a sample of 69 people with an error rate of 10 percent. Data collection was carried out using observation and questionnaires. The data analysis techniques used are descriptive statistics and inferential statistics. The results of this research indicate that the implementation of excellent service in the Universitas Negeri Makassar library is considered sufficient, in terms of aspects of reliability, communication, response and understanding of users. User satisfaction at the Universitas Negeri Makassar library is considered to be poor in terms of ease of obtaining information, speed of obtaining information and information provision services. There is a significant positive effect of implementing excellent service on user satisfaction at the Universitas Negeri Makassar Library Technical Implementation Unit (UPT), namely 55.3 percent.